Megapixel X-ray ghost imaging with a prior-recorded reference - Tang, Jie; Zhang, Haipeng; Zhao, Changzhe; Zhao, Nixi; Wu, Jianwen; Guo, Han; Xiao, Tiqiao (Frontiers in Physics, 2025)
IntroductionEfficient implementation of X-ray ghost imaging (XGI) with megapixel-level field-of-view and spatial resolution of few microns is key towards practical applications of XGI, but such implementation remains constrained by the time-consuming data acquisition and low-quality reconstruction for megapixel images under insufficient overall sampling rates.MethodsWe propose an efficient implementation scheme based on synthetic aperture X-ray ghost imaging (SAXGI), in which only one set of prior-recorded reference images is needed for ghost imaging of multiple objects.ResultsExperimental results demonstrated that images of three different objects, including tungsten fiber, resolution chart and small fish, can be successfully reconstructed with the same set of prior-recorded references, which implicates that the efficiency of data acquisition can be improved significantly. Taking advantage of SAXGI, image size of 2040 × 1440 pixels and system resolution of 10 μm was achieved. Results of a small fish show that comparable image quality is achieved with a sampling rate of 27.6%, which means that the radiation dose is reduced to about 1/4 of a conventional radiography. Furthermore, an extreme sampling rate down to 0.5% is enough to make out the skeleton of the fish, which further demonstrates high robustness and the low-dose potential of the proposed method for X-ray imaging.ConclusionsIn conclusion, the proposed method with a prior-recorded reference is applicable for XGI of multiple samples and the data acquisition efficiency is greatly improved. Through further hardware improvement of the imaging system, SAXGI with a prior-recorded reference is anticipated to provide an efficient solution for megapixel X-ray ghost imaging.